Analisis strategi guru dalam implementasi pendidikan karakter peduli sosial peserta didik kelas v sekolah dasar - Deny Kurniadi Saputro; Jenny Poerwanti; Siti Kamsiyati (Didaktika Dwija Indria, 2023)
AbstractThe teacher's strategy in implementing socially caring character education for students includes habituation patterns, giving reprimands, exemplary, strengthening as well as for outside there are routine activities, providing exemplary outside of learning and environmental conditioning. The purpose of this study is, (1) to analyze the teacher's strategy in implementing social care character education for students. (2) Describe the constraints of the teacher's strategy in implementing socially caring character education for students. (3) Describe how to overcome the teacher's strategic constraints in implementing socially caring character education for fifth grade students at SD Negeri 1 Sukorejo. This research is a type of descriptive qualitative research. Researchers conducted observations, questionnaires, and documentation. Data analysis uses data reduction, data presentation, then draws conclusions. The data validity technique uses technique and source triangulation. The results showed that: (1) Overall the teacher had not implemented or seen from his strategy in implementing student character education because certain obstacles were found. (2) Obstacles in the teacher's strategy in implementing social care character education for students in general that were found were the emotions of children or students who were not yet stable at their age and time constraints for implementation. (3) The way to overcome the obstacles found in the teacher's strategy for implementing socially caring character education in general is to control students and conditions according to the conditions between the teacher and students.